Mesenchymal stem cell interaction with Ti6Al4V alloy pre-exposed to simulated body fluid. Issue 12 (13th February 2020) - Jarolimova, Petra; Voltrova, Barbora; Blahnova, Veronika; Sovkova, Vera; Pruchova, Eva; Hybasek, Vojtech; Fojt, Jaroslav; Filova, Eva
Abstract : Titanium and its alloys are widely used for substitution of hard tissues, especially in orthopaedic and dental surgery. Abstract : Titanium and its alloys are widely used for substitution of hard tissues, especially in orthopaedic and dental surgery. Despite the benefit of the use of titanium for such applications, there are still questions which must be sorted out. Surface properties are crucial for cell adhesion, proliferation and differentiation. Mainly, micro/nanostructured surfaces positively influence osteogenic differentiation of human mesenchymal stem cells. Ti6 Al4 V is a biocompatible α + β alloy which is widely used in orthopaedics. The aim of this study was to investigate the interaction of the nanostructured and ground Ti6 Al4 V titanium alloys with simulated body fluid complemented by the defined precipitation of hydroxyapatite-like coating and to study the cytotoxicity and differentiation capacity of cells with such a modified titanium alloy. Nanostructures were fabricated using electrochemical oxidation. Human mesenchymal stem cells (hMSC) were used to evaluate cell adhesion, metabolic activity and proliferation on the specimens. The differentiation potential of the samples was investigated using PCR and specific staining of osteogenic markers collagen type I and osteocalcin. Our results demonstrate that both pure Ti6 Al4 V, nanostructured samples, and hydroxyapatite-like coating supported hMSC growth and metabolic activity. Nanostructured samples improved collagen type I synthesis after 14 days, while both nanostructured and hydroxyapatite-like coated samples enhanced collagen synthesis on day 21. Osteocalcin synthesis was the most enhanced by hydroxyapatite-like coating on the nanostructured surfaces. Our results indicate that hydroxyapatite-like coating is a useful tool guiding hMSC osteogenic differentiation.